Consumption in China how China's new consumer ideology is shaping the nation - Yu, LiAnne (Cambridge, [England] Polity Press, 2014)
Explores what it means to be a consumer in the world's fasting growing economy, the emotional and social triggers behind consumption, and the impact of increased consumption on the country.
1 Introduction -- 2 Spaces -- 3 Status -- 4 Lifestyles -- 5 Commodification -- 6 Awareness -- 7 Consumption with Chinese Characteristics.
Keywords: Consumption (Economics) -- China; Consumers -- China; Consumer behavior -- China